Principles of supervision in cognitive behavioural therapy - Prasko, Jan; Vyskocilova, Jana; Slepecky, Milos; Novotny, Miroslav (Biomedical papers, 2012)
Background: Psychotherapy requires clinical supervision. This is systematic guidance of a therapist by a supervisor. Inevitably, there is a question of training new high-quality therapists. This is related to supervision of their basic training. Later, it is important to provide an opportunity for lifelong supervision throughout the entire psychotherapeutic practice.Method: PUBMED data base was searched for articles using the key words ``supervision in CBT'', ``therapeutic relations'', ``transference'', ``countertransference'', ``schema therapy'', ``dialectical behavioral therapy''. The search was repeated by changing the key word. No language or time constraints were applied. The lists of references of articles detected by this computer data base search were examined manually to find additional articles. We also used the original texts of A. T. Beck, J. Beck, M. Linehan, R. Leahy, J. Young and others. Basically this is a review with conclusions about supervision in cognitive behavioral therapy.Results: The task of supervision is obvious - to increase the value of the therapeutic process in the client's best interest. At the same time, supervision is an educational process in the truest sense of the word, including an opportunity to select one's own supervisor. This is a very important procedural aspect since the therapist identifies with his/her supervisor, either consciously or unconsciously. Establishing the supervisor-supervisee relationship is based on principles similar to those in the therapeutic relationship. There is an important parallel reflecting the therapist-client relationship. This is because any changes in the supervisory process are analogically transferred onto the therapist-client relationship. Additionally, supervision is oriented towards increasing the therapist's competencies. The CBT therapist's basic skills involve good theoretical knowledge, professional behaviour towards clients, ability to use specific therapeutic strategies for maintaining the therapeutic relationship, sensitivity to parallel processes and accomplishment of changes, and adherence to ethical norms. Given the fact that during supervision, the supervisee may be in any stage of his/ her training, supervision must take into consideration where the therapist is in his/her training and development and what he/she has or has not learnt.Conclusions: Both the literature and our experience underscore the importance of careful supervision of cognitive behavioral therapy. The supervisory relationship is similar to a therapeutic relationship and the supervisee also needs security, acceptance and appreciation for his/her professional growth. However, there is more freedom in the relationship. Supervision may only lead to the supervisee's professional growth if it supports his/her individuality and helps him/her to discover things. Therefore, numerous approaches are used in supervision which are associated with the abilities to self-reflect and to realize transference and countertransference mechanisms.
Keywords: supervision; cognitive behavioural therapy; competencies; supervisory relationship; transference; counter transference